Laterite-nickel ore pellet sintering method based on solid phase and liquid phase coupling consolidation
By adding magnetite tailings and low-carbon ferrochromium smelting slag into the laterite nickel ore pellet sintering process, the chemical composition is adjusted, the liquid phase generation temperature is reduced, and the liquid phase content is increased, thereby solving the problem of yield and drum problems in the existing technology. It solves the problem of low strength and realizes efficient and low-cost sinter preparation.
Patent Information
- Application Number
- CN202411442939.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing laterite nickel ore fire process, the yield and drum strength of limonite-type laterite nickel ore are relatively low, making it difficult to meet the high-quality and low-cost needs of nickel-ferroalloy smelting.
A laterite nickel ore pellet sintering method based on solid phase and liquid phase coupled solidification is used to adjust the chemical composition of the mixed material through magnetite tailings and low carbon ferrochromium smelting slag, reduce the liquid phase generation temperature, and increase the liquid phase content. Thereby improving the yield of sinter and drum strength.
It has achieved a yield of more than 75% and a drum strength of more than 60% for sintered pellets, which has reduced solid fuel consumption, improved production efficiency, and effectively utilized solid waste, in line with the concept of green and sustainable development.
Smart Images

Figure CN119332082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and more particularly to a laterite nickel ore pellet sintering method based on solid-liquid coupled consolidation. Background Art
[0002] Nickel is widely used in industrial production due to its excellent physical and chemical properties. It is not only used to manufacture stainless steel and alloy structural steel, but also an important component of batteries. With the rapid development of emerging industries such as new energy electric vehicles, the market demand for nickel continues to expand. Land-based nickel ores are divided into two categories: sulfide nickel ores and laterite nickel ores. Due to long-term mining, the reserves of sulfide nickel ores with higher comprehensive utilization value have seriously declined, so laterite nickel ores have become the focus of global nickel resource development. my country is a major producer of stainless steel and new energy vehicles. Nickel resources have long relied on imports, with a foreign dependence of more than 80%. Foreign restrictions on the export of rich laterite nickel ores have made most of my country's imports low-grade laterite nickel ore resources, namely limonite-type laterite nickel ores.
[0003] The current laterite nickel ore pyrometallurgical process mainly includes the rotary kiln-electric furnace process and the sintering-blast furnace process. The characteristics of high iron and low nickel of limonite-type laterite nickel ore make it unsuitable for the rotary kiln-electric furnace process. Therefore, relevant researchers have conducted a series of studies on the sintering-blast furnace process. Among them, in the patent CN115537555A, by adding an aluminum source or directly using high-aluminum laterite nickel ore, the aluminum content in the sintering raw material is adjusted, the liquid phase generation temperature is reduced, the liquid phase generation amount is increased, the sintering ore mineralization conditions are improved, and the sintering ore strength of the laterite nickel ore is improved, so as to provide high-quality and low-cost limonite-type laterite nickel ore sinter for nickel-iron alloy smelting. In the patent CN114540614A, the laterite nickel ore is ball-milled, mixed with the laterite nickel ore magnetic separation tailings and slaked lime to make balls, and then the solid fuel is wrapped on the surface of the raw ball, and then the sintering test is carried out, so as to fully improve the permeability of the sintering material layer and the combustion conditions and effects of the solid fuel, thereby effectively improving the sintering ore strength and output and reducing its solid fuel consumption. However, the yield and drum strength of the sintered ore finally obtained by the above two methods are still relatively low, and further improvement is needed.
[0004] Therefore, providing a method for preparing limonite-type laterite nickel ore pellets with high yield and drum strength is a problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of this, the present invention provides a laterite nickel ore pellet sintering method based on solid-liquid coupled consolidation, wherein the method adjusts the chemical composition of the mixed material through magnetite tailings and low-carbon ferrochrome smelting slag, reduces the formation temperature of the liquid phase during sintering, and increases the liquid phase content, thereby obtaining a sintering pellet sintering process with high yield and high drum strength.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation comprises the following steps:
[0008] S1, mixing limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in proportion;
[0009] S2, adding appropriate amount of water to the mixed raw materials to make balls to obtain green balls;
[0010] S3, rolling the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel;
[0011] S4, the green balls wrapped with solid fuel are distributed, ignited, sintered and cooled in sequence to obtain sintered ore, and the sintered ore is crushed and granulated to obtain finished pellets.
[0012] The pelletizing sintering process of the present invention pre-pellets the mixture and then wraps the solid fuel on the surface of the pellets, which can not only effectively improve the air permeability of the sintering material layer; but also avoid the occurrence of deep wrapping of fuel particles by mineral powder particles, thereby greatly improving the combustion conditions and effects of the solid fuel, and thus effectively reducing the solid fuel consumption of the sintered ore; in addition, the strength of the green balls in the pelletizing sintering process is higher than that of the mixture in the ordinary process, which is more conducive to the formation of sintered ore with higher strength.
[0013] The limonite-type laterite nickel ore described in S1 is required to have a particle size of less than 0.074 mm, accounting for more than 80%; the magnetite tailings and low-carbon ferrochrome smelting slag are required to have a particle size of less than 0.074 mm, accounting for more than 90%.
[0014] The mass ratio of the limonite-type laterite nickel ore, magnetite tailings and low-carbon ferrochrome smelting slag is 70-74:4-7:11-14.
[0015] Its beneficial effect is that silicon is used to reduce chromium and iron oxides in low-carbon ferrochrome smelting, and the compound SiO 2 At the same time, in order to improve the recovery rate of chromium, a large amount of quicklime needs to be added, so the CaO and SiO in the low-carbon ferrochrome smelting slag 2 The content of components is high. The magnetite tailings contain high SiO 2 , CaO, and MgO. By adding the two to adjust the ratio of the chemical components in the mixed material, during the sintering process of the mixed material, Ca magnesium feldspar with a low melting point is generated. 2 Mg(CO 3 ) 2 and calcium forsterite (Ca,Mg) 2 Si 2 O 6The eutectic temperature of the spinel phase and magnesia-ferrocene is lower than 1300℃, so a liquid phase will be generated when sintered at around 1300℃, which will serve as the bonding phase of the sintered ore, thereby improving its yield and drum strength.
[0016] In S2, a disc ball making machine is used for ball making, the ball making time is 9 to 15 minutes, the moisture content of the raw balls is 18 to 20%, and the particle size of the raw balls is 10 to 12 mm.
[0017] The solid fuel described in S3 is anthracite, and it is required that the particle size below 3 mm accounts for more than 70%, and the amount thereof is 4.0-6.0% of the total material mass.
[0018] The thickness of the cloth layer in S4 is 700-900 mm.
[0019] The ignition temperature is 1100°C, the ignition time is 3 minutes, the ignition negative pressure is 8KPa, the sintering temperature is 1300°C-1350°C, the time is 8-12 minutes, the sintering exhaust negative pressure is 10KPa, and after sintering is completed, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3 minutes.
[0020] After the crushing and granulation described in S4, the particles are dropped three times continuously at a height of 2m, and are screened and classified. The +5mm part is the finished pellet, and the -5mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0021] The present application also seeks to protect the laterite nickel ore pellets prepared by the above method, wherein the yield of the pellets reaches more than 75% and the drum strength reaches more than 60%.
[0022] It can be seen from the above technical solution that, compared with the prior art, the present invention discloses a laterite nickel ore pellet sintering method based on solid-liquid coupled consolidation, which has the following beneficial effects:
[0023] (1) Limonite-type laterite nickel ore contains a certain amount of Al 2 O 3 However, the MgO content is relatively low. In the existing sintering technology, quicklime is generally added as a flux. The liquid phase after sintering is composed of 2CaO·Al 2 O 3 ·SiO 2 The main phase is calcium aluminum feldspar, which has a high melting point and is not suitable as a bonding phase. In this application, magnetite tailings and low-carbon ferrochrome smelting slag are added, and CaO and SiO in the low-carbon ferrochrome smelting slag are added. 2 The content of components is high, SiO in magnetite tailings 2 , CaO, and MgO content is high, and the liquid phase of the mixed material after sintering will be Ca 2 Mg(CO 3 ) 2and calcium forsterite (Ca,Mg) 2 Si 2 O 6 Mainly, the melting points of the two are lower and they are more suitable as bonding phases.
[0024] (2) The present invention generates calcium magnesium orthoclase Ca with a low melting point during sintering. 2 Mg(CO 3 ) 2 and calcium forsterite (Ca,Mg) 2 Si 2 O 6 As a binding phase, it reduces the temperature of liquid phase formation, can generate sufficient liquid phase when sintered at 1300℃, improves the strength of the pellets, and the yield of the prepared pellets can reach more than 75%, and the drum strength can reach more than 60%.
[0025] (3) The solid fuel is wrapped around the surface of the green ball, and then a sintering test is carried out. In the test, the strength of the green ball is significantly higher than that of the general sintering mixture. In addition, wrapping the solid fuel can fully improve the permeability of the sintering material layer and the combustion conditions and effects of the solid fuel, thereby effectively improving the strength and output of the sintered ore, while reducing the fuel consumption of the solid fuel.
[0026] (4) In this application, solid wastes such as magnetite tailings and low-carbon ferrochrome smelting slag are fully utilized to adjust the chemical composition of the mixed materials, thereby reducing production costs and complying with the concept of green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Process flow chart of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The chemical compositions of the raw materials used in the following examples are as follows:
[0030] Limonite-type laterite nickel ore contains 65.67% TFe, 1.21% Ni, and Cr 2 O 3 5.46%, CaO 0.96%, MgO1.51%, Al 2 O 3 8.77%, SiO 2 2.9%.
[0031] TFe 9.35%, CaO 16.48%, MgO 16.02%, Al 2 O 3 7.65%, SiO 2 25%.
[0032] TFe 1.3%, Cr in low carbon ferrochrome smelting slag 2 O 3 4.15%, CaO 48.35%, MgO 6.9%, Al 2 O 3 9.03%, SiO 2 29%.
[0033] The raw materials are ball-milled separately, wherein the limonite-type laterite nickel ore is required to have a particle size of less than 0.074 mm, accounting for more than 80%; the magnetite tailings and low-carbon ferrochrome smelting slag are required to have a particle size of less than 0.074 mm, accounting for more than 90%; the solid fuel is anthracite, and the particle size is required to be less than 3 mm, accounting for more than 70%.
[0034] Example 1
[0035] (1) Mix limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in a weight ratio of 72:5.4:12.6.
[0036] (2) A disc ball making machine is used to add appropriate amount of water to the mixed raw materials for ball making. The ball making time is 9 minutes, the moisture content of the raw balls is 20%, and the particle size of the raw balls is 10 mm.
[0037] (3) Roll the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel, and the amount of solid fuel used is 4.0% of the total material mass.
[0038] (4) The green balls wrapped with solid fuel are placed, ignited, sintered and cooled in sequence to obtain sintered ore. The sintered ore is crushed and granulated. The particles are dropped three times from a height of 2 m and sieved and graded. The +5 mm part is the finished pellet and the -5 mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0039] The thickness of the cloth material layer is 900mm. The ignition temperature is 1100℃, the ignition time is 3min, the ignition negative pressure is 8KPa, the sintering temperature is 1350℃, the time is 8min, the sintering exhaust negative pressure is 10KPa, and after sintering, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3min.
[0040] The sintering indexes of pellet sintering process are: drum strength 63.51%, finished product rate 76.11%, and utilization coefficient 1.67t·m -2 ·h -1 .
[0041] Example 2
[0042] (1) Mix limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in a weight ratio of 70:7:11.
[0043] (2) A disc ball making machine is used to add appropriate amount of water to the mixed raw materials for ball making. The ball making time is 15 minutes, the moisture content of the raw balls is 18%, and the particle size of the raw balls is 12 mm.
[0044] (3) Roll the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel, and the amount of solid fuel used is 6.0% of the total material mass.
[0045] (4) The green balls wrapped with solid fuel are placed, ignited, sintered and cooled in sequence to obtain sintered ore. The sintered ore is crushed and granulated. The particles are dropped three times from a height of 2 m and sieved and graded. The +5 mm part is the finished pellet and the -5 mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0046] The thickness of the cloth material layer is 900mm. The ignition temperature is 1100℃, the ignition time is 3min, the ignition negative pressure is 8KPa, the sintering temperature is 1350℃, the time is 12min, the sintering exhaust negative pressure is 10KPa, and after sintering is completed, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3min.
[0047] The sintering indexes of pellet sintering process are: drum strength 63.15%, finished product rate 76.89%, and utilization coefficient 1.62t·m -2 ·h -1 .
[0048] Example 3
[0049] (1) Mix limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in a weight ratio of 72:5.4:12.6.
[0050] (2) A disc ball making machine is used to add appropriate amount of water to the mixed raw materials for ball making. The ball making time is 15 minutes, the moisture content of the raw balls is 18%, and the particle size of the raw balls is 12 mm.
[0051] (3) Roll the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel, and the amount of solid fuel used is 6.0% of the total material mass.
[0052] (4) The green balls wrapped with solid fuel are placed, ignited, sintered and cooled in sequence to obtain sintered ore. The sintered ore is crushed and granulated. The particles are dropped three times from a height of 2 m and sieved and graded. The +5 mm part is the finished pellet and the -5 mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0053] The thickness of the cloth material layer is 700mm. The ignition temperature is 1100℃, the ignition time is 3min, the ignition negative pressure is 8KPa, the sintering temperature is 1300℃, the time is 12min, the sintering exhaust negative pressure is 10KPa, and after sintering is completed, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3min.
[0054] The sintering indexes of pellet sintering process are: drum strength 60.21%, finished product rate 75.08%, and utilization coefficient 1.63t·m -2 ·h -1 .
[0055] Example 4
[0056] (1) Mix limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in a weight ratio of 74:4:11.
[0057] (2) A disc ball making machine is used to add appropriate amount of water to the mixed raw materials for ball making. The ball making time is 9 minutes, the moisture content of the raw balls is 18%, and the particle size of the raw balls is 10 mm.
[0058] (3) Roll the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel, and the amount of solid fuel used is 4.0% of the total material mass.
[0059] (4) The green balls wrapped with solid fuel are placed, ignited, sintered and cooled in sequence to obtain sintered ore. The sintered ore is crushed and granulated. The particles are dropped three times from a height of 2 m and sieved and graded. The +5 mm part is the finished pellet and the -5 mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0060] The thickness of the cloth material layer is 700mm. The ignition temperature is 1100℃, the ignition time is 3min, the ignition negative pressure is 8KPa, the sintering temperature is 1350℃, the time is 8min, the sintering exhaust negative pressure is 10KPa, and after sintering, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3min.
[0061] The sintering indexes of pellet sintering process are: drum strength 60.53%, finished product rate 75.14%, and utilization coefficient 1.71t·m -2 ·h -1 .
[0062] Comparative Example 1
[0063] (1) Limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag are mixed in a mass ratio of 72:5.4:12.6, and then 4.0% of anthracite by mass of the total material is added and mixed evenly.
[0064] (2) A disc pelletizing machine is used to add an appropriate amount of water to the mixed raw materials for pelletizing. The pelletizing time is 9 minutes and the pelletizing particle size is 10 mm to obtain the balls to be sintered.
[0065] (3) The ore to be sintered is placed, ignited, sintered, and cooled in sequence to obtain sintered ore. The sintered ore is crushed and granulated, and the particles are dropped three times from a height of 2 m. After screening and grading, the +5 mm part is the finished pellet, and the -5 mm part is the returned ore. Finally, the relevant sintering indicators are tested.
[0066] The thickness of the cloth material layer is 900mm. The ignition temperature is 1100℃, the ignition time is 3min, the ignition negative pressure is 8KPa, the sintering temperature is 1300℃, the time is 8min, the sintering exhaust negative pressure is 10KPa, and after sintering is completed, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3min.
[0067] The sintering indexes of pellet sintering process are: drum strength 55.71%, finished product rate 70.02%, and utilization coefficient 1.52t·m -2 ·h -1 .
[0068] By comparing the data of Comparative Example 1 and Example 1, it can be seen that the quality of the pellets prepared by wrapping the solid fuel on the surface of the green ball and then conducting the sintering test is obviously better than the pellets produced by mixing the solid fuel with laterite nickel ore to make balls and then sintering. This is because wrapping the solid fuel can fully improve the permeability of the sintering material layer and the combustion conditions and effects of the solid fuel, thereby effectively improving the strength and output of the sintered ore and reducing its solid fuel consumption.
[0069] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0070] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation, characterized in that: The steps include: S1, mixing limonite-type laterite nickel ore, magnetite tailings, and low-carbon ferrochrome smelting slag in proportion; S2, adding appropriate amount of water to the mixed raw materials to make balls to obtain green balls; S3, rolling the obtained green balls with solid fuel to obtain green balls wrapped with solid fuel; S4, the green balls wrapped with solid fuel are placed, ignited, sintered and cooled in sequence to obtain sintered ore, and the sintered ore is crushed and granulated to obtain finished pellets.
2. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: The limonite-type laterite nickel ore described in S1 is required to have a particle size of less than 0.074 mm, accounting for more than 80%; the magnetite tailings and low-carbon ferrochrome smelting slag are required to have a particle size of less than 0.074 mm, accounting for more than 90%.
3. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: The mass ratio of the limonite-type laterite nickel ore, magnetite tailings and low-carbon ferrochrome smelting slag described in S1 is 70-74:4-7:11-14.
4. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: In S2, a disc ball making machine is used for ball making, the ball making time is 9 to 15 minutes, the moisture content of the raw balls is 18 to 20%, and the particle size of the raw balls is 10 to 12 mm.
5. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: The solid fuel described in S3 is anthracite, and it is required that the particle size below 3 mm accounts for more than 70%, and the amount thereof is 4.0-6.0% of the total material mass.
6. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: The thickness of the cloth layer in S4 is 700-900 mm.
7. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: The ignition temperature in S4 is 1100°C, the ignition time is 3 minutes, the ignition negative pressure is 8KPa, the sintering temperature is 1300°C~1350°C, the time is 8~12 minutes, the sintering exhaust negative pressure is 10KPa, and after sintering is completed, the cooling negative pressure is adjusted to 5KPa and the cooling time is 3 minutes.
8. The method for sintering laterite nickel ore pellets based on solid-liquid coupled consolidation according to claim 1, characterized in that: After crushing and granulation in S4, the particles fall down three times continuously at a height of 2m. After screening and grading, the +5mm part is the finished pellets, and the -5mm part is the returned ore. Finally, the relevant sintering indicators are tested.
9. A laterite nickel ore pellet prepared by the method according to any one of claims 1 to 8, characterized in that: The finished product rate of the pellets reaches more than 75%, and the drum strength reaches more than 60%.
Citation Information
Patent Citations
Method for sintering limonite type laterite-nickel ore pellets
CN114540614A
Method for strengthening sintering of limonite type laterite-nickel ore
CN115537555A